Clinical methods of cryopreservation for donor lymphocyte infusions vary in their ability to preserve functional T‐cell subpopulations. Issue 6 (28th April 2017) - Worsham, D. Nicole; Reems, Jo‐Anna; Szczepiorkowski, Zbigniew M.; McKenna, David H.; Leemhuis, Thomas; Mathew, Aby J.; Cancelas, Jose A.; ,
Abstract : BACKGROUND: Cryopreserved donor lymphocyte infusion (DLI) products are manufactured and administered to treat relapse after allogeneic hematopoietic stem cell transplantation. Reported clinical responses to DLIs vary broadly, even within the same group of patients. While there is an implicit recognition of the fact that different manufacturing protocols may have specific effects on different cell types, cryopreservation protocols are frequently derived from our experience in the cryopreservation of stem cell products and do not account for the heterogeneous functional nature of DLI T‐cell populations. Here, we report the results of a prospective, multicenter trial on the effect of four different cryopreservation solutions that were used to freeze DLIs compared to control DLIs that were refrigerated overnight. STUDY DESIGN AND METHODS: Cryopreserved postthawed and refrigerated specimens were analyzed side by side for their T‐cell subpopulation content and viability, as well as T‐cell proliferation, cytokine secretion, and cytotoxic activities. RESULTS: This study indicates that "homemade" 10% dimethyl sulfoxide (DMSO) results in reduced viability of different CD4+ T‐cell populations, including T‐helper, T‐cytotoxic, and T‐regulatory populations, and a decrease in their proliferative and cytotoxic response to immunologically relevant stimuli, while the use of solutions containing 5% DMSO with intracellular‐like cryoprotectant stabilizers maintains T‐cell function at levels similar to refrigerated control samples. CONCLUSION: This study has important implications in determining the best cryoprotectant solution for specific clinical applications in allogeneic immunotherapy.